PELAKSANAAN EKSEKUSI BENDA JAMINAN SETELAH LELANG HAK TANGGUNGAN PADA BALAI MANDIRI PRASARANA BALI - Sucipto Sun; Kt. Sukawati Lanang P. Perbawa (Jurnal Hukum Mahasiswa, 2023)
In providing credit to the community, both individuals and business entities, banks need to request collateral as a guarantee of credit repayment by the debtor. In accordance with Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Related to Land (UUHT), the process of providing collateral is carried out by installing Mortgage Rights. The existence of Mortgage Rights authorizes the bank as a creditor to sell the object of Mortgage collateral through an auction to pay off the debtor's debt if the debtor is in default. The research method used is empirical juridical using data sourced from the Private Auction Office in Denpasar City.